2014
DOI: 10.2478/acph-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability of two oral formulations of clopidogrel: Determination of clopidogrel and its carboxylic acid metabolite (SR26334) under fasting and fed conditions in healthy subjects

Abstract: Clopidogrel, a thienopyridine derivative, is a potent antiplatelet drug that inhibits adenosine diphosphate (ADP)-mediated platelet activation and aggregation by selectively and irreversibly binding to platelet P2Y 12 purinergic receptor (1). Results of a large clinical trial have demonstrated an overall benefit of clopidogrel over aspirin in the prevention of vascular ischemic events (myocardial infarction, stroke, vascular death) in patients with a history of symptomatic atherosclerotic disease (2). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The observed decreases in the clopidogrel acid AUC 0– t and AUC inf , as well as the delayed t max , are consistent with reduced clopidogrel solubility and a slight decrease in absorption caused by increased gastric pH with SZC. A previous study observed similar changes when clopidogrel was administered with food [ 30 ]. In fed versus fasted studies, clopidogrel acid C max decreased by 10–16% without altering the antiplatelet activity of clopidogrel [ 30 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The observed decreases in the clopidogrel acid AUC 0– t and AUC inf , as well as the delayed t max , are consistent with reduced clopidogrel solubility and a slight decrease in absorption caused by increased gastric pH with SZC. A previous study observed similar changes when clopidogrel was administered with food [ 30 ]. In fed versus fasted studies, clopidogrel acid C max decreased by 10–16% without altering the antiplatelet activity of clopidogrel [ 30 ].…”
Section: Discussionsupporting
confidence: 54%
“…A previous study observed similar changes when clopidogrel was administered with food [ 30 ]. In fed versus fasted studies, clopidogrel acid C max decreased by 10–16% without altering the antiplatelet activity of clopidogrel [ 30 ]. During coadministration of clopidogrel with PPIs that do not inhibit cytochrome P450 (e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Several previous studies have tested the bioequivalence of new generic clopidogrel against Plavix ® tablets 3 , 17 , 18 or the antiplatelet effect of other salts. 5 , 19 The aim of this study was to test the bioavailability of new generic clopidogrel 75 mg tablet versus the reference Plavix.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were conducted in healthy participants covering a wide dosing range, SD and MD, intravenous and peroral administration. Considering the digitized studies, training [ 23 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and test datasets [ 42 , 44 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] were defined for development and evaluation of the clopidogrel model, respectively. The training dataset preferably included profiles reporting many measurement points over a long period of time and studies quantifying multiple metabolites of interest.…”
Section: Methodsmentioning
confidence: 99%